The everyday life of the Kalmyk State University named after B.B. Gorodovikov in the article by E. Badmaeva, E. Omakaeva «The anthropological microcosm of university everyday life in the era of the late USSR (1970-1980-IES): towards the formulation of the problem (by the example of the scientific community in the steppe region)» - A. D. Osmaev (Nomadic Civilization: Historical Research)
.